Respostas

  • Usuário do Brainly
2013-12-02T19:13:25-02:00
A= -1 b= -2   c=3
formula de baskara -b +- v b2-4ac/ 2a
2+- v 4-4x-1x 3/ 2 x-1
2+- v 16 / -2
2+- 4 / -2
a resposta sao duas raizes 2+4/2 = -3         2-4/-2 = 1

Obs: v é raiz quadrada

2013-12-02T20:30:01-02:00
- x² - 2x + 3 = 0
a= -1
b= -2
c= 3

x= -(-2) + - V -2² - 4 . - 1 . 3/ 2 . -1
x= 2 + - V 4 + 12 / - 2
x = 2 + - V16 / - 2
x = 2 + - 4 / - 2 
x' = 2 + 4 / - 2 = 6/ - 2 = x( - 1) = - 6/ 2 = - 3
x" = 2 - 4 / -2 = - 2 / - 2 = x( -1) = 2/2 = 1